PERAN BIMBINGAN DAN KONSELING KRISTEN DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SEKOLAH KRISTEN - Sylvia Su Siaw Chee; Prisman Sapu’; Srikandi Larasati; Juliwen Sinta; Dwy Giovani Tonapa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to examine the role of Christian guidance and counseling in character formation for students in Christian schools. Character formation is one of the main goals of Christian education, which focuses not only on academic development but also on students' moral and spiritual growth. This study used a qualitative method with a library research approach. Data were obtained from various literature sources, including books, scientific journals, and research findings relevant to Christian guidance and counseling and character education. The study results indicate that Christian guidance and counseling plays a significant role in helping students understand their identity based on Christian values, develop character that reflects the teachings of Christ, overcome various problems that hinder personal development, and strengthen spiritual growth. The implementation of services through individual counseling, group guidance, spiritual development, educator role models, and collaboration with families and churches has been proven to support the holistic formation of student character. Therefore, Christian guidance and counseling is an important part of realizing the goals of Christian education, which is oriented towards the formation of individuals with character and faith.